ПАТРИОТИЧЕСКОЕ ВОСПИТАНИЕ В КАЗАХСТАНЕ И СТРАНАХ БЛИЖНЕГО ЗАРУБЕЖЬЯ - Рузиева, Д.И.; Арзымбетова, Ш.М.; Даулеталиева, Д.М. (SCIENCE and SOCIETY, 2022)
Popularization of patriotism and its values. Patriotic education in the near abroad. The contribution of each people to the prosperity of the country and the land, ancestral traditions, descendants.